Surveillance of tick-borne encephalitis virus foci in Slovakia: A seroprevalence study in ruminants combined with virus detection in ticks - Martina Ličková; Bronislava Víchová; Markéta Derdáková; Monika Sláviková; Sabína Fumačová Havlíková; Dana Zubriková; Diana Selyemová; Michal Chvostáč; Lucia Blaňarová; Viktória Čabanová; Veronika Vaňová; Lucia Šulejová; et al. (Ticks and Tick-Borne Diseases)
The tick-borne encephalitis virus (TBEV) is an important human pathogen that causes tick-borne encephalitis, a potentially fatal neurological disease. Human infections occur through tick bites or after the consumption of raw milk products from infected animals, causing alimentary outbreaks representing a significant public health problem in Slovakia. In the present study, a total of 1029 ruminant sera (from 672 sheep and 357 goats) from 18 localities, collected in Slovakia during 2017–2019 were initially screened for TBEV-specific antibodies by ELISA, and 98 (9.5 %) of them were confirmed as positive by the plaque reduction neutralization test or immunofluorescence assay. The differences in observed seroprevalence of 11.9 % (80/672) among sheep and of 5.0 % (18/357) among goats were significant. Tick screening was subsequently conducted near the surveyed farms where seropositive animals were identified. Overall, 2,534 ticks (2,528 Ixodes ricinus, 3 Dermacentor reticulatus, 2 Dermacentor marginatus, 1 Haemaphysalis concinna) from 7 collection sites were pooled and analysed by RT-qPCR, resulting in estimated prevalence of 2.86 % (ranging from 0.31 to 8.72 % at different sites). The estimated prevalence in adults was lower (2.15 %) than in nymphs (2.9 %). Positive ticks (all I. ricinus) and milk samples were then used for virus isolation. Three new cell culture isolates were prepared and sequenced. Obtained full-length genome sequences revealed high genetic diversity and phylogenetic clustering with virus strains found across Europe. The seroprevalence of TBEV in farm animals is an effective tool for identifying areas of virus circulation and guiding more in-depth field investigations of local tick populations. This combined approach of serological and virological surveillance provides valuable data for assessing the risk of alimentary TBEV infections and characterizing local TBEV strains.